2023
DOI: 10.3390/en16041569
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics, Kinetic Modeling, Energy and Exergy Analyses of Water Yam (Dioscorea alata) in a Hot Air Dryer

Abstract: In this study, drying characteristics, kinetic modelling, energy and exergy analyses of a convective hot air dryer are presented for water yam. The drying experiments were carried out at temperature levels of 50, 60, and 70°C and slice thicknesses of 3, 6, and 9 mm. The effects of drying variables on the drying rate (DR), moisture diffusivity (Deff), activation energy (Ea), energy utilization (EU), energy utilization ratio (EUR), exergy loss (EXL), exergy efficiency (EXeff), improvement potential (IP), and exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It can be seen in the figure that the microstructure's pore-like structure gradually increased with the thickness of the slices, and the pore-like structure was most clearly visible at 2 mm. The reasons may be that thin slices are more quickly and evenly heated; the heat can be rapidly transferred to each part of the yam slices; the moisture needs to pass through a shorter distance; the migration rate is faster; and it is easy to form a large number of delicate pores [55]. On the contrary, the temperature difference between the interior and exterior of thicker slices may be more significant, resulting in insufficient internal heat transfer and a lower rate of moisture migration, and the process of moisture evaporation may lead to contraction of the internal structure, and thus, a reduction in the number and size of holes.…”
Section: Effect Of Different Slice Thicknesses On Rehydration Ratio O...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen in the figure that the microstructure's pore-like structure gradually increased with the thickness of the slices, and the pore-like structure was most clearly visible at 2 mm. The reasons may be that thin slices are more quickly and evenly heated; the heat can be rapidly transferred to each part of the yam slices; the moisture needs to pass through a shorter distance; the migration rate is faster; and it is easy to form a large number of delicate pores [55]. On the contrary, the temperature difference between the interior and exterior of thicker slices may be more significant, resulting in insufficient internal heat transfer and a lower rate of moisture migration, and the process of moisture evaporation may lead to contraction of the internal structure, and thus, a reduction in the number and size of holes.…”
Section: Effect Of Different Slice Thicknesses On Rehydration Ratio O...mentioning
confidence: 99%
“…This caused the center to be heated slowly and dried unevenly, resulting in over-drying of the outer layer, while the center still contained water. Over-drying of the outer layer may lead to cell wall disruption and structural hardening, which reduces the ability of water to enter the yam slices after drying [55]. Figure 10 shows the effect on the microstructure of yam slices at different slice thicknesses.…”
Section: Effect Of Different Slice Thicknesses On Rehydration Ratio O...mentioning
confidence: 99%
“…During grain drying, moisture is transferred from a whole grain to the air and the latent heat required to vaporize the moisture is supplied by the drying air [4]. Thus, drying is a simultaneous process of heat and mass transfer [5][6]. It is important to understand the changes in the grain temperature and MC and to clarify the effects of drying conditions during the grain drying process, as this may be useful in improving the efficient use of current grain dryers and developing new grain dryers; therefore, mathematical modeling is very important.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous available food drying mathematical models such as the Page equation, the Newton model, the Wang and Singh model, and so on [5,7]. A number of empirical equations developed have as good, or greater, accuracy in a specific application with less computational effort compared with theoretical equations [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that reducing the cooling duty in the middle stages of the propane operator could result in energy savings of up to 13.5% compared to the base case. Several scholars conducted assessments on the energy and exergy efficiencies within diverse agricultural productions such as onion (Kaveh et al, 2021), green peas (Kaveh et al, 2020), potato (Golpour et al, 2020), wheat (Yan et al, 2023), cantaloupe (Zadhossein et al, 2023), water yam (Okunola et al, 2023) and vermicelli (Kumar et al, 2023). Vilarinho et al (2017) carried out an evaluation on the pre-distillation unit by analyzing its energy and exergy.…”
Section: Introductionmentioning
confidence: 99%